2021
DOI: 10.1002/tafs.10318
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Tailbeat Frequencies of Three Fish Species from Adaptive Resolution Imaging Sonar Data

Abstract: Imaging sonars, such as the Adaptive Resolution Imaging Sonar (ARIS), provide high-resolution sonar data that are used in fisheries research and management. While sonar methods have enormous potential for making population estimates, species identification via sonar remains an unresolved challenge. One method that may overcome this challenge involves measuring tailbeat frequencies to guide species differentiation. The tailbeat frequencies of three commonly sympatric anadromous fish species of eastern North Ame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Able et al, 2014; Egg et al, 2017; Helminen et al, 2020; Kang, 2011; Mueller et al, 2010; Parsons et al, 2017). Helminen et al (2021) and Mueller et al (2010) demonstrated the potential of this approach and successfully calculated tail beat frequencies from data collected using an ARIS and DIDSON respectively. However, the utility of this technique is likely to change between sites because fish may alter their behaviour in different environments (Helminen et al, 2021) and background noise levels will affect the ability to discern tail beats (Mueller et al, 2010).…”
Section: Capabilities Of Acoustic Cameras For Monitoring Fish Around ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Able et al, 2014; Egg et al, 2017; Helminen et al, 2020; Kang, 2011; Mueller et al, 2010; Parsons et al, 2017). Helminen et al (2021) and Mueller et al (2010) demonstrated the potential of this approach and successfully calculated tail beat frequencies from data collected using an ARIS and DIDSON respectively. However, the utility of this technique is likely to change between sites because fish may alter their behaviour in different environments (Helminen et al, 2021) and background noise levels will affect the ability to discern tail beats (Mueller et al, 2010).…”
Section: Capabilities Of Acoustic Cameras For Monitoring Fish Around ...mentioning
confidence: 99%
“…stands in contrast with taxonomic classification of fishes in optical camera imagery, where classification can often be performed based on a single image. Several studies have proposed the use of tail beat frequency as a quantitative behavioural metric that may aid in classification (e.g Able et al, 2014;Egg et al, 2017;Helminen et al, 2020;Kang, 2011;Mueller et al, 2010;Parsons et al, 2017). Helminen et al (2021.…”
mentioning
confidence: 99%
“…However, the tailbeat frequency generally overlaps among different species. Other features such as migrating time and shape should be combined (Helminen et al, 2021). The feature‐based methods are straightforward for species identification, but the reported morphological and motion features are not good enough to distinguish similar fishes.…”
Section: Applications In Fish Monitoringmentioning
confidence: 99%
“…2014; Helminen et al. 2021; Helminen and Linnansaari 2021). They can remain operational over a broader range of stream conditions (e.g., high‐flow periods) compared to weir counting (Pipal et al.…”
mentioning
confidence: 99%
“…2020; Helminen et al. 2021). Combining sonar with other methods, such as fishing or underwater video cameras (UWCs), is used to estimate the abundance of each species in fixed‐location sonar applications within rivers (Mueller et al.…”
mentioning
confidence: 99%